Mobile robot motion planning by point to point based on modified ant colony optimization and Voronoi diagram - Habib, Nukman; Purwanto, Djoko; Soeprijanto, Adi (2016 International Seminar on Intelligent Technology and Its Applications (ISITIA), 2016)
The basic purpose of mobile robot motion planning (MRMP) is discover the shortest path safely from beginning to the end position in the environment without crash some obstacles. In this paper, we proposed a combined method between Voronoi diagram (VD) and the modified Ant Colony Optimization (M-ACO) algorithm for MRMP. The Voronoi diagram generate edges and vertices in the obstacles-filled space, then M-ACO choose the nodes (the generated vertices by VD) to form the safely shortest path by point to point (PTP) motion planning. The proposed approach to solve this MRMP problem indicate that it could make a safely planning shortest path.